2021
DOI: 10.1177/01979183211044096
|View full text |Cite
|
Sign up to set email alerts
|

Collectivized Discretion: Seeking Explanations for Decreased Asylum Recognition Rates in Finland After Europe's 2015 “Refugee Crisis”

Abstract: In 2015, during the so-called “refugee crisis” in Europe, Finland was among the European countries receiving exceptionally large numbers of asylum applications. As the volume of asylum applications surged, however, the percentage of positive asylum decisions in Finland declined substantially. In this article, we explore reasons for this dramatic drop in recognitions rates and examine Finnish immigration control authorities’ use of discretion in asylum credibility assessment. Our approach is unique in its appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Notwithstanding a significant drop in detention orders due to mobility restrictions following the COVID-19 pandemic, detention has been a routine police measure in immigration enforcement in Finland: around 1250 foreign nationals were detained annually during the 2010s, accounting for roughly half of all effective removals in many years (Police of Finland, 2022). Immigration detention has been affiliated with the asylum system in Finland, in particular after the arrival of a record number of 32,136 asylum seekers in 2015 (around 10 times more than in previous years) and subsequent harsh changes in the recognition rates for international protection (Näre, 2020; Vanto et al, 2022). While most removal decisions have followed rejected asylum applications—in particular, for Afghan, Iraqi, and Somalian citizens—individual situations of detained foreign nationals vary considerably.…”
Section: Immigration Detention In Finlandmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding a significant drop in detention orders due to mobility restrictions following the COVID-19 pandemic, detention has been a routine police measure in immigration enforcement in Finland: around 1250 foreign nationals were detained annually during the 2010s, accounting for roughly half of all effective removals in many years (Police of Finland, 2022). Immigration detention has been affiliated with the asylum system in Finland, in particular after the arrival of a record number of 32,136 asylum seekers in 2015 (around 10 times more than in previous years) and subsequent harsh changes in the recognition rates for international protection (Näre, 2020; Vanto et al, 2022). While most removal decisions have followed rejected asylum applications—in particular, for Afghan, Iraqi, and Somalian citizens—individual situations of detained foreign nationals vary considerably.…”
Section: Immigration Detention In Finlandmentioning
confidence: 99%
“…Alongside specific deterrence for deportable individuals, immigration detention is also an instrument of general deterrence for other deportable subjects in the country by manifesting coercive consequences for noncompliance (see Leerkes and Broeders, 2010). However, the actual removability has constrained the detention of certain nationalities: in particular, Iraq and Afghanistan have only readmitted voluntarily returning citizens and individuals deported due to criminal offenses (see Näre, 2020; Vanto et al, 2022). In fact, the detention of Iraqi and Afghan asylum seekers has mainly been related to transfers to other EU countries under the Dublin regulation (Police of Finland, 2022).…”
Section: Different Applications Of Immigration Detentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of investigative journalists at the beginning of the crisis indicated that caseworkers employed as a result of the emergency appointments in 2016 were given templates of negative asylum decisions (Yle News, 2017). Indeed, a comparison between the asylum decisions before and after the so-called crisis (Vanto et al, 2022) revealed that asylum caseworkers' assessment of similar facts changed considerably. In particular, trust in the credibility of applicants' claims decreased.…”
Section: Harmful Analogue Solutionsmentioning
confidence: 99%
“…Notably, there were no legal changes that could explain this interpretative shift. The considerable scope of discretion given to immigration officers allowed them to draw on legal frameworks in a flexible and instrumental manner and, under the political pressure to curb the increased number of arrivals, generated a shift in asylum decision making on a grand scale (Vanto et al, 2022).…”
Section: Harmful Analogue Solutionsmentioning
confidence: 99%